A neural circuit for gastric motility disorders driven by gastric dilation in mice - Wang, Xi-yang; Chen, Xiao-qi; Wang, Guo-quan; Cai, Rong-lin; Wang, Hao; Wang, Hai-tao; Peng, Xiao-qi; Zhang, Meng-ting; Huang, Shun; Shen, Guo-ming (Frontiers in Neuroscience, 2023)
Introduction Symptoms of gastric motility disorders are common clinical manifestations of functional gastrointestinal disorders (FGIDs), and are triggered and exacerbated by stress, but the neural pathways underpinning them remain unclear. Methods We set-up a mouse model by gastric dilation (GD) in which the gastric dynamics were assessed by installing strain gauges on the surface of the stomach. The neural pathway associated with gastric motility disorders was investigated by behavioral tests, electrophysiology, neural circuit tracing, and optogenetics and chemogenetics involving projections of the corticotropin-releasing hormone (CRH) from the paraventricular nucleus of the hypothalamus (PVN) to acetylcholine (ChAT) neurons in the dorsal motor nucleus of the vagus (DMV). Results We found that GD induced gastric motility disorders were accompanied by activation of PVNCRH neurons, which could be alleviated by strategies that inhibits the activity of PVNCRH neurons. In addition, we identified a neural pathway in which PVNCRH neurons project into DMVChAT neurons, modulated activity of the PVNCRH→DMVChAT pathway to alleviate gastric motility disorders induced by GD. Discussion These findings indicate that the PVNCRH→DMVChAT pathway may mediate at least some aspects of GD related gastric motility, and provide new insights into the mechanisms by which somatic stimulation modulates the physiological functions of internal organs and systems.